MANAGEMENT MODEL IN VIPASSANA MEDITATION TRAINING PROGRAMS OF PROVINCIAL MEDITATION PRACTICE CENTERS IN NONTHABURI PROVINCE - (Nuntakit Teepungkaro), PhrakruVirotkanchanaket; Phrakruophatnonthakit; Boonpoo, Somsak (Journal of Educational Review Faculty of Education in MCU, 2023)
The objectives of this dissertation were 1) to study the conditions of management in Dhamma practice centers, 2) to develop a management model in vipassana meditation training programs of provincial meditation practice centers in Nonthaburi province, and 3) to propose a management model in vipassana meditation training programs of provincial meditation practice centers in Nonthaburi province. Mixed methodology research. The quantitative data were collected by questionnaires from 297 samples and analyzed by percentage, mean, and standard deviation. The qualitative data were obtained by interviews with 10 experts, and focus group discussions with 6 experts. Analyzed by content analysis. The study results were found that; 1) the conditions of management in Dhamma practice centers in overall and each aspect was at a high level, sorted from descending to the top; control, administration, planning, organization, and personnel. Management model in vipassana meditation training programs of provincial meditation practice centers in Nonthaburi province consisted of 4 parts: introduction, model, implementation steps, and success condition. 3)Management model in vipassana meditation training programs of provincial meditation practice centers in Nonthaburi province is a management principle that consists of planning, organizing, personnel, administration, controlling, and integrating according to the 4 Satipatthana principles, making vipassana meditation training programs of provincial meditation practice centers in Nonthaburi province more efficient.